Determinación de la capacidad killer de levaduras nativas y la posible utilización de Saccharomyces cerevisiae (killer) y Hanseniaspora uvarum (killer) en la producción de bioetanol (2021)
Colombia is a tropical country, rich in biodiversity, thanks to the great variety of ecosystems that exist in it, with approximately 314 types of ecosystems in Colombia, according to data from the Ministry of Sciences and Technology (2019). This biodiversity makes possible the use of microorganisms with agroindustrial potential, among these, yeasts stand out where there are a large number of genera and species that can be used to obtain products with high added value. Yeasts are unicellular fungi capable of producing enzymes and other compounds, they are widely used in the food industry (Bakery, production of fermented beverages), pharmaceutical, biotechnological and for the production of ethanol (bioethanol) (Suárez-Machín, Garrido-Carralero, & Guevara-Rodríguez, 2016). Among yeasts there is a group capable of secreting a protein toxin that affects the cell wall of socalled sensitive yeasts, this group is known as killer yeasts, the greatest importance of this group lies in the impossibility of contamination by a large number of microorganisms, being that these yeasts have a diversity of functions such as biological controllers since, due to their killer capacity, it eliminates other contaminating microorganisms from important agro-industrial processes such as the production of Bioethanol, they facilitate the production of wines in addition to the production of ethanol. This is why, for the production of bioethanol, a killer yeast is ideal, finding that some varieties of Saccharomyces cerevisiae meet these characteristics. This yeast is characterized by being chemoganotrophic, anaerobic and facultative and is capable of using different sugars, in addition to being an organism that is easy to grow, with rapid growth and great adaptability, ideal for the production of bioethanol, since this is the product end of the alcoholic fermentation carried out by this microorganism with good production yields. In this work, the aim was to isolate the yeast strains which were later characterized and identified morphologically, biochemically and molecularly. From this characterization the strains of Saccharomyces cerevisiae that possess killer characteristics and their capacity for the production of bioethanol were selected. For the above, in the microbiology laboratory of the San Buenaventura Cali University, the yeasts were isolated from agroindustrial fruits (Vittis vinícola, Annona muricata and Psidium guajava) and the characterization of the yeast colonies and the morphology was carried out. of them, through the use of the microscope and stereoscope, identifying both macroscopic and microscopic characteristics. For the biochemical identification, sowings and growths were carried out in specific culture medium related in the Pitt and Hockings identification key, while the molecular identification was carried out in the research laboratory of the San Buenaventura Cali University, using for DNA extraction the Soil DNA Isolation Plus Kit, this DNA was replicated by means of PCR For the above, in the microbiology laboratory of the San Buenaventura Cali University, the yeasts were isolated from agroindustrial fruits (Vittis vinícola, Annona muricata and Psidium guajava) and the characterization of the yeast colonies and the morphology was carried out. of them, through the use of the microscope and stereoscope, identifying both macroscopic and microscopic characteristics. For the biochemical identification, sowings and growths were carried out in specific culture media related in the Pitt and Hockings identification key, while the molecular identification was carried out in the research laboratory of the San Buenaventura Cali University, using for DNA extraction the Soil DNA Isolation Plus Kit, this DNA was replicated by means of PCR (Polymerase chain reaction) and sent to MacroGen for further sequencing. The sequence alignment of the yeast strains was carried out with the BLAST software, it was expected to identify the genus and species of the isolated strains. Subsequently, the Saccharomyces cerevisiae strains were selected to determine the killer capacity where they were inoculated in the form of groove and then the selected strains were added together with a control yeast. Finally, the bioethanol production was determined by the selected strains with a controlled fermentation, using molasses as the culture medium and determining the concentration of ethanol obtained by means of HPLC. The killer capacity and the ethanol concentration obtained from the isolated yeasts were compared with those expressed with the type yeasts reported in the literature and which are currently commonly used for the production of bioethanol.